Carex rigescens caffeic acid O-methyltransferase gene CrCOMT confer melatonin-mediated drought tolerance in transgenic tobacco - Li, Yan; Sun, Yan; Cui, Huiting; Li, Mingna; Yang, Guofeng; Wang, Zengyu; Zhang, Kun (Frontiers in Plant Science, 2022)
Melatonin is an important, multifunctional protective agent against a variety of abiotic and biotic stressors in plants. Caffeic acid O-methyltransferase (COMT) catalyzes the last step of melatonin synthesis in plants and reportedly participates in the regulation of stress response and tolerance. However, few studies have reported its function in melatonin-mediated drought resistance. In this study, CrCOMT was identified and was strongly induced by drought stress in Carex rigescens. CrCOMT overexpression in transgenic tobacco increased tolerance to drought stress with high levels of seed germination, relative water content, and survival rates. CrCOMT overexpression in tobacco improved membrane stability, and plants exhibited lower relative electrolytic leakage and malondialdehyde content, as well as higher photosynthetic efficiency than the wildtype (WT) under drought stress. The transgenic plants also had higher levels of proline accumulation and antioxidant enzyme activity, which decreased oxidative stress damage due to reactive oxygen species (ROS) hyperaccumulation under drought stress. The transcription of drought stress response and ROS scavenging genes was significantly higher in the CrCOMT overexpression plants than in the WT plants. In addition, CrCOMT transgenic tobacco plants exhibited higher melatonin content under drought stress conditions. Exogenous melatonin was applied to C. rigescens under drought stress to confirm the function of melatonin in mediating drought tolerance; the relative water content and proline content were higher, and the relative electrolytic leakage was lower in melatonin-treated C. rigescens than in the untreated plants. In summary, these results show that CrCOMT plays a positive role in plant drought stress tolerance by regulating endogenous melatonin content.